DEVELOPMENT OF INFORMATION TECHNOLOGY FOR COMPLEX EVALUATION OF HIGHER EDUCATION INSTITUTIONS - Valeriy Yu. Bykov; Oleksandr Yu. Kuchanskyi; Andrii O. Biloshchytskyi; Yurii V. Andrashko; Oleksandr V. Dikhtiarenko; Svitlana V. Budnik (Інформаційні технології і засоби навчання, 2019)
This paper presents a method for complex evaluation of higher education institutions based on a generalized volume of m-simplex calculation. Every kind of activities of higher education institutions (educational, scientific, innovative, etc.) determines an axis in the multidimensional space used to build the m-simplex. After evaluating higher education institutions in the specified m-activities, the points are put on the respective axis. M-simplex with vertices in these points is built. The generalized volume of this m-simplex, which is calculated based on the Cayley-Menger determinant, defines the integral quantitative assessment of higher education institutions’ activities. To verify the specified method for evaluating higher education institutions, we reviewed well-known evaluation methods and described some types of activities that could be used as a basis for a definition of the axes on which the m-simplex is built. The research component of higher education institutions’ activities is determined by the volume of articles published and their citations in international scientometric databases. The educational component relates to the quality of graduates, their competitiveness in the labour-market. The international component concerns the participation of higher education institutions and their departments in international programs and projects. The described method could be used to monitor the activities of higher education institutions and their separate structural subdivisions. The results of the monitoring are important for a comprehensive evaluation of scientific, educational, international, innovative and other types of activities of higher education institutions in a particular region and the country as a whole. In this article, we have formed a list of indicators, according to which several Ukrainian higher education institutions were evaluated. Besides, the comparison of quantitative evaluations with ratings of higher education institutions in international systems of university activities evaluation was made.